Support Architecture for Second Screen Apps Dynamic Adaptation - Valente, Carlos Eduardo Viana; Souza, Cidcley Teixeira de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
The dynamics of social networks have increasingly driven TV viewers to interact while watching their favorite shows. By using polls, chats, news and other mechanisms in order to dialogue more directly with these viewers. However, social networks provide only a partial way of interaction for this type of media, since they were not designed to deal with the peculiarities of TV programs. To such purpose Second Screen applications were created, and they can be understood as an extension of the TV screen in which any information or interactions can be presented to users through apps for smartphones or tablets. Unlike social networks, Second Screen apps are made available by broadcasters specifically for TV users. For TV Stations, it is necessary to develop several applications in order to cover the various programs in their schedule, and as a consequence this generates expenses to companies, which may explain the massive use of social networks by these broadcasters in order to interact with viewers nowadays. Therefore, this paper aims at presenting a supporting architecture to a dynamic update of a generic Second Screen app. Such architecture enables the deployment of broadcasters, programs, media, quizzes and any other Second Screen features without the need to create new apps by broadcasters or install new apps by users. The results demonstrated several benefits that the versatility of the proposed architecture offers to all those involved in the chain of television content production.